(untitled) (JULACE: Journal of the University of Namibia Language Centre, 2018)
This conceptual paper deals with some theoretical configurations and considerations of the form and content of African popular culture/s. It problematizes the subject by raising some provocative questions that may produce further and, perhaps, new areas for discussions. The three leading questions are: What exactly is popular culture? For whom and by what means is such culture produced and consumed? To whom and to what end is such culture popular? The paper touches on questions of identity, especially pertaining to the youth; and the link between popular culture and social, political and economic power. Further, the paper deals with aspects of production, including mass production, and consumption of popular culture. The role of popular culture in the political processes is interrogated in terms of mobilization, resistance, articulation and maintenance of identities that provide alternative ways of interpreting different social forces. Issues of nationalism and national culture in the face of “globalization” are also touched on vis-à-vis African popular cultures. We also ask whether we should view the subject from purely anti-elitist and pro-masses outlook. Generally the paper probes into the place of popular culture within the bigger definition of culture as a drapery of physical, mental and emotional actions whose nexus holds a particular people together within and oftentimes across generations.